2017
DOI: 10.1302/1863-2548-11-160281
|View full text |Cite
|
Sign up to set email alerts
|

Slipped capital femoral epiphysis management and the arthroscope

Abstract: BackgroundIn situ pinning of slipped capital femoral epiphysis (SCFE) results in various degrees of deformity of the femoral head-neck junction. Repetitive trauma from cam-type femoroacetabular impingement (FAI) can lead to labral tears and injury to the articular cartilage causing loss of function. Arthroscopic osteoplasty is an alternative to open procedure and to Southwick/Imhäuser-type osteotomies in symptomatic selected cases.Surgical techniqueThe amount of bone to be resected has to be carefully planned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Recent studies have reported encouraging outcomes of contemporary surgical approaches including hip arthroscopy 1820,2729,37 and SHD 6,2126 but limited comparative data is available. Our findings demonstrated that symptomatic improvement can be achieved after arthroscopy for mild deformity and after surgical dislocation with or without an osteotomy for moderate and severe deformities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported encouraging outcomes of contemporary surgical approaches including hip arthroscopy 1820,2729,37 and SHD 6,2126 but limited comparative data is available. Our findings demonstrated that symptomatic improvement can be achieved after arthroscopy for mild deformity and after surgical dislocation with or without an osteotomy for moderate and severe deformities.…”
Section: Discussionmentioning
confidence: 99%
“…17 Contemporary techniques include osteochondroplasty through an arthroscopic approach 1820 or through a surgical hip dislocation (SHD) approach with or without a combined proximal femoral osteotomy. 21,22 Prior studies looking at the outcome of deformity correction after SCFE consist of case series of both open 6,2126 and arthroscopic techniques 19,20,2729 with relatively good outcomes reported for both. However, there are limited comparative studies 30 and the treatment of symptomatic FAI secondary to healed SCFE remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Osteochondroplasty can be performed arthroscopically with a drill or by limited anterior arthrotomy using a modified Smith-Peterson approach. [9][10][11][12] After surgery, patients have to relieve the affected limb for 6-12 weeks using crutches or walkers. This allows you to maintain the treatment result and achieve proper union.…”
Section: Diagnosticsmentioning
confidence: 99%
“…Likewise, patients with mild, stable slips may present years after SCFE onset, without previously seeking treatment. Osteochondroplasty through controlled surgical hip dislocation, as originally described by Ziebarth et al [33], has been found in short-term follow-up studies to improve joint mobility, hip pain, and radiographic alpha angles in patients with FAI who have a history of SCFE [2,30]. One major advantage of this approach is that intertrochanteric osteotomy may be performed concomitantly, if necessary.…”
Section: Introductionmentioning
confidence: 99%